The characteristics and antigenic properties of recently emerged subclade 3C.3a and 3C.2a human influenza A(H3N2) viruses passaged in MDCK cells - Lin, Yipu (2017)
Fil: Lin, Yipu. The Francis Crick Institute, London; Reino Unido.